Analysis of Millennial Purchase Intention Using Modified UTAUT2 in Yogyakarta City - Lusia Tria Hatmanti Hutami; Bernadetta Diansepti Maharani (Inovbiz: Jurnal Inovasi Bisnis, 2021)
The purpose of this study was to analyse the effect of hedonic motivation and online purchasing habits on online purchase intentions and the effect of habitual mediation on hedonic motivation and online purchase intentions by Millennial. The research method used the AMOS path analysis to 400 students at the Universitas Sarjanawiyata Tamansiswa, Yogyakarta. The results showed that all hypotheses were accepted except hedonic motivation towards online purchase intentions, while habitual mediation of hedonic motivation and online purchase intentions was accepted, thus strengthening this mediation relationship. Thus, it can be concluded that Millennial like the online shopping experience because it is considered fun and amusing and can lead to habitual behaviour. The implication for online purchasing application managers should not only prioritize short-term (momentary) relationships but prioritize long-term relationships therefore consumers become accustomed to using the application. The author's recommendation for managers is to always be creative and innovative, such as creating an attractive and profitable membership program. This research is limited to the number and distribution area of the sample and does not specifically refer to a particular application. Suggestions for further research include the impact of social relationships and the facilitating conditions applied to online purchase intentions.